Medical malpractice related to dialysis and vascular access: An analysis of lawsuit judgements in South Korea. - Ji Eun Kim (Public Library of Science (PLoS), 2021)
Background Hemodialysis is a life-saving renal replacement treatment for patients with chronic kidney disease, but various complications occur during hemodialysis and associated procedures. This study was conducted to analyze the specific characteristics of hemodialysis-related complications and malpractice that have led to legal disputes. Methods Judgments from cases litigated between 1991 and 2019 due to complications related to hemodialysis or vascular access were analyzed using the database of the Korean Supreme Court Judgment System. Results Of 32 dialysis-related litigation cases, 14 cases were dismissed and malpractice was recognized in 18 cases. Among all cases and those in which malpractice was recognized, the most common clinical complication was associated with central venous catheter (CVC) insertion (25.0% and 42.9%, respectively). In 22 of 32 (68.8%) cases, complications occurred before or after (not during) dialysis, and performance error was the most common clinical error leading to legal disputes (58.3%). Complications resulted in death in 59.4% of cases, and CVC-related complications were associated with the largest proportion (63.2%) of deaths. Conclusions Hemodialysis was implicated in various medical disputes, and CVC-related complications were the most common and serious adverse events. Clinicians' awareness of the incidence and severity of possible complications of hemodialysis procedures should be increased.